HUBUNGAN BUDAYA ORGANISASI DENGAN KINERJA PEGAWAI DI KANTOR WALIKOTA MANADO - SAROINSONG, MOUREN VRYSLA; LALOMA, ALDEN; RURU, JOORIE MARHAEN (JURNAL ADMINISTRASI PUBLIK, 2015)
ABSTRAKOrganizational culture is a norm or various types of regulations to improve andcontrol the performance of employees in the agency, but in reality there are employeeswhose performance does not match the organizational culture in the institution enacted.departed from the matter, this study are intended to answer the question whetherorganizational culture is closely linked to the performance of civil servants in the officeof the mayor of Manado.This research uses quantitative methods.The research done by taking 60 respondents in the mayor's office in the captureManado randomly in the Regional Secretariat on 12 sections / agencies. collecting datausing questionnaires roebuck aids interview techniques. ata analysis using staticticanalysis , linear regression , and the product moment correlation. pengelolahan dataanalysis using manual calculation formula based on statistical analysis , linear regression ,and the product moment correlationBased on the analysis of the data : (1) The regression coefficient cultural relationsorganization with the performance of civil servants in the amount of 0.654 scale / unit. (2)based on the analysis of the data : 1. The regression coefficient cultural relationsorganization with the performance of civil servants in the amount of 0.654 scale / unit ;while the determination coefficient is 0.32 or 32 % of the results of these studiesconcluded that cultural relations organization with the performance of civil servants , apositive and significant impact on employee performanceBased on these conclusions, responsive local government is very needed incontrolling as well as re-evaluating the performance results of the employees to be moreon the increase.Key words: organizational culture, Employee Performance